2019
DOI: 10.1002/ecs2.2564
|View full text |Cite
|
Sign up to set email alerts
|

Mistletoe generates non‐trophic and trait‐mediated indirect interactions through a shared host of herbivore consumers

Abstract: Indirect interactions emerge among a wide range of herbivores sharing the same plant resource. Consumers usually belong to different trophic guilds, from folivores and sapsuckers to parasitic plants. We propose that mistletoes parasitizing pines could play a key role acting as herbivores on host pines and coming indirectly into competition with other herbivores feeding on the same host. Changes caused by mistletoes on its host have been well studied, but its effects running across trophic webs remain unreveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…), making host leaves less attractive for herbivorous insects (Lázaro‐González et al . ). These differences in resource quantity and quality can be expected to increase the abundance of herbivores and detritivores likely represented in the most responsive arthropod groups found in pit‐fall traps – that is, Coleoptera, Hemiptera, Diplopoda, and litter‐dwelling Lepidoptera larvae.…”
Section: Discussionmentioning
confidence: 97%
“…), making host leaves less attractive for herbivorous insects (Lázaro‐González et al . ). These differences in resource quantity and quality can be expected to increase the abundance of herbivores and detritivores likely represented in the most responsive arthropod groups found in pit‐fall traps – that is, Coleoptera, Hemiptera, Diplopoda, and litter‐dwelling Lepidoptera larvae.…”
Section: Discussionmentioning
confidence: 97%
“…Qualitatively, mistletoe brings to the forest stand new species, mostly belonging to the orders Hymenoptera, Diptera, Lepidoptera (floral visitors) and Hemiptera (herbivores and predator), while quantitatively it provides twice as many arthropods as appear in the canopy of the unparasitised pines. While mistletoe attracts a new community of specialists, different from host pine (Lázaro‐González et al ., 2017), mistletoe parasitism causes detrimental indirect effects on pine‐feeding herbivores across its shared host, suggesting a worsening of host quality as food (Lázaro‐González et al ., 2019a, b). These changes (i.e.…”
Section: Concluding Comments: Mistletoe As An Attractor Of Biodiversimentioning
confidence: 99%
“…In functional terms, mistletoe adds to the pine canopy two plant–animal interactions with mutualistic consequences that do not occur in the pine forest without mistletoe: the pollination derived from floral visitor's activities during the early spring, and the dispersion of seeds derived from the frugivorous bird activity during autumn and winter (Mellado & Zamora, 2014, 2016, 2017). Thus, with mistletoe, a relatively simple pine canopy, dominated by antagonistic plant–herbivorous interactions with a limited number of species involved (Lazaro‐González et al ., 2017, 2019b), becomes a complex bank ( sensu Darwin, 1859) of plant–animal interactions of different signs, with a marked role of mutualistic interactions such as pollination and zoochory. In this way, mistletoe creates conditions that support the co‐occurrence of functionally distinct organisms in the canopies, fostering pine forest biodiversity and complexity.…”
Section: Concluding Comments: Mistletoe As An Attractor Of Biodiversimentioning
confidence: 99%
See 1 more Smart Citation
“…Parasitism by the hemiparasitic plant mistletoe decreases the food quality of the host by causing enhanced indirect defense (Lázaro‐González et al 2019 a ) and reductions in mineral nutrient availability (Mutlu et al 2016). Lázaro‐González et al (2019 b ) demonstrated that parasitism by the mistletoe Viscum album subsp. austriacum reduced feeding damage to pine caused by aphids, moth larvae, and weevils.…”
Section: Figmentioning
confidence: 99%